2013
DOI: 10.1177/0956797612466414
|View full text |Cite
|
Sign up to set email alerts
|

Foraging for Thought

Abstract: Processing of a target stimulus may be inhibited if its location has just been cued, a phenomenon of spatial attention known as inhibition of return (IOR). Here, we demonstrate a striking effect wherein items that have just been the focus of reflective attention (internal attention to an active representation) are also inhibited. Participants saw two items, followed by a cue to think back to (refresh, direct reflective attention toward) one item, and then had to identify either the refreshed item, the unrefres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
120
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(135 citation statements)
references
References 26 publications
15
120
0
Order By: Relevance
“…The results also corroborate recent evidence that WM representations can act like attended stimuli [36]–[38], but now uncover a neurobiologically plausible mechanism for selective WM maintenance: namely the center-surround configuration likely arising from lateral inhibition that analogously focuses visual attention on representations of task-relevant stimuli in the environment. The results reported herein present compelling evidence that WM processes abide by core properties of attentional selection, which may directly reflect biased competitive dynamics of local neuronal populations, and thus open several avenues of future inquiry into the neurophysiological mechanisms that allow us to select and process information ‘in mind’.…”
Section: Discussionsupporting
confidence: 87%
“…The results also corroborate recent evidence that WM representations can act like attended stimuli [36]–[38], but now uncover a neurobiologically plausible mechanism for selective WM maintenance: namely the center-surround configuration likely arising from lateral inhibition that analogously focuses visual attention on representations of task-relevant stimuli in the environment. The results reported herein present compelling evidence that WM processes abide by core properties of attentional selection, which may directly reflect biased competitive dynamics of local neuronal populations, and thus open several avenues of future inquiry into the neurophysiological mechanisms that allow us to select and process information ‘in mind’.…”
Section: Discussionsupporting
confidence: 87%
“…M. K. Johnson and colleagues reported that refreshing of a just-presented item yielded better long-term memory compared to the re-presentation of the item for reading (Grillon, Johnson, Krebs, & Huron, 2008;M. K. Johnson, Reeder, Raye, & Mitchell, 2002;M. R. Johnson et al, 2013).…”
Section: What Is Free Time Being Used For?mentioning
confidence: 99%
“…In a second step, we confirmed that internal selective attention is intrinsically involved in searching through the serial order representation in WM. From the notion that there is direct interfacing between internal and external selective attention (Downing, 2000 ; Awh and Jonides, 2001 ; Corbetta and Shulman, 2002 ; Nobre et al, 2006 ; Johnson et al, 2013 ; Kiyonaga and Egner, 2013 ; Van der Lubbe et al, 2014 ), we combined a similar WM manipulation as described above with the well-known Posner cuing paradigm—typically used to study (external) spatial selective attention (Posner et al, 1982 ). In the Posner paradigm, it has been shown that an attention cue (for example a centrally presented arrow) presented shortly before a to-be-detected dot appears left or right on the screen, facilitates performance when it cues the subsequent dot location validly, but impairs performance when it cues the opposite location.…”
Section: Serial Order Working Memory and Spatial Processingmentioning
confidence: 99%